2001
DOI: 10.1038/sj.cgt.7700382
|View full text |Cite
|
Sign up to set email alerts
|

Local inflammation and devascularization — in vivo mechanisms of the “bystander effect” in VPC-mediated HSV-Tk/GCV gene therapy for human malignant glioma

Abstract: Somatic gene therapy with the herpes simplex virus type I thymidine kinase gene/ganciclovir (HSV-Tk/GCV) system and murine retroviral vector producer cells (VPCs) was introduced as a new adjuvant treatment modality to treat tumor bulk and to prevent tumor recurrence in patients harboring malignant glioma. The single-center experience after treatment of 27 patients undergoing tumor resection followed by intracerebral VPC injection for HSV-Tk suicide gene therapy will be presented focused on findings of systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 18 publications
(15 reference statements)
1
27
0
Order By: Relevance
“…Gene therapy has become a promising strategy for the treatment of gastric cancer [27][28][29][30][31] , in which the transfer of suicide genes into tumor cells has emerged as an attractive modality for the selective elimination of cancer cells [14][15][16]30,31] . The suicide genes encode non-mammalian enzymes that can convert nontoxic prodrugs into cellular toxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene therapy has become a promising strategy for the treatment of gastric cancer [27][28][29][30][31] , in which the transfer of suicide genes into tumor cells has emerged as an attractive modality for the selective elimination of cancer cells [14][15][16]30,31] . The suicide genes encode non-mammalian enzymes that can convert nontoxic prodrugs into cellular toxic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…One of the landmark discoveries for this therapeutic strategy is the transfer of suicide genes, such as HSV-TK, into the tumor cells, which has been shown to exert antitumor efficacy on a variety of cancer cells [8][9][10][11] . The expressed HSV-TK/ganciclovir (GCV) system can not only inhibit the DNA synthesis of the target cells but also produce a bystander effect against tumors [12][13][14][15][16] . However, these effects have been found to be unstable in some of the transfected cells, which may result in a decreased efficiency in the treatment of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…9 Success of this approach in animal tumor models has led to clinical trials in a variety of tumor types. [22][23][24][25] An important feature of this form of enzyme-prodrug therapy is that HSV-TK-expressing cells can cause GCVmediated cytotoxicity in tumor cells that do not express the transgene, a process known as the bystander effect. 10,[26][27][28] Bystander cytotoxicity is critical for the enzyme-prodrug gene therapy strategy because current techniques for gene transfer typically result in fewer than 10% of the cells expressing the transgene.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide gene therapy with the herpes simplex virus thymidine kinase (HSV-TK) fragment, the most widely used strategy for the cancer therapeutic study [3] , has been shown to exert antitumor efficacy in various cancer models [4][5][6][7] . However, its efficacy seems not to be fully developed to eliminate tumor cells in some of the investigations [8][9][10][11][12] . Gene therapy with HSV-TK and cytokine genes together may produce a complementary effect, and has become a new insight for the treatment of malignancies [13,14] .…”
Section: Introductionmentioning
confidence: 99%